Common blue nevus of the uterine cervix - A report of 16 cases - Kubelka-Sabit, Katerina; Basheska, Neli; Hadzi-Nicheva, Biljana; Grncharovska, Zlata; Prodanova, Irina; Jashar, Dzengis; Zografski, George (Macedonian Association of Anatomists and Morphologists, 2005)
Blue nevus is uncommon pigmented lesion of the skin that rarely appears in the different mucoses, such as cervix or vagina. Sixteen cases of cervical blue nevi were diagnosed in our department in a five-year period (2000-2004). Localized in the stroma of the cervical canal, predominantly in the posterior lip, the lesions measured 0.1-2 cm. Prussian blue stain excluded the presence of hemosiderin and Masson-Fontana, S100 and HMB-45 stains confirmed the melanocytic nature of the lesions. Our findings are similar to those published in several studies. The recognition of this obscure lesion prevents its misinterpretation as siderosis or malignant melanoma.
Син невус на грлото на матката - Приказ на 16 случаи
Keywords: blue nevus; uterine cervix; histochemistry; immunohistochemistry; differential diagnosis